Monetary/fiscal policy regimes in post-war Europe - Othman Bouabdallah; Pascal Jacquinot; Valeria Patella (European Central Bank (ECB), 2023)
In most euro area countries, the monetary/fiscal policy mix is responsible for the changing history of debt and inflation facts. Using a Dynamic Stochastic General Equilibrium model with Markov-switching policy rules, we identify three distinct monetary/fiscal regimes in France and Italy: a Passive Monetary-Active Fiscal regime (PM/AF) before the late 80s/early 90s; an Active Monetary-Passive Fiscal regime (AM/PF) with central bank independence and EMU convergence; a third regime with policy rates at the effective lower bound combined with fiscal active behaviour to sustain the recovery. Our simulations reveal that the PM/AF regime in France led to price volatility and debt stabilisation, while the AM/PF regime resulted in disinflation and rising debt trajectory. Meanwhile, Italy's procyclical fiscal policy in downturns contributed to persisting imbalances, high aggregate volatility, and low growth.
Keywords: E63; E62; E32; E52; C32; 330; Monetary-Fiscal policy mix; euro area; Debt; Inflation; Markov-switching